Randomized, Double‐Blind, Placebo‐Controlled, Dose‐Escalating Phase I, Healthy Subjects Study of Intravenous OPN‐305, a Humanized Anti‐TLR2 Antibody - Reilly, M; Miller, R M; Thomson, M H; Patris, V; Ryle, P; McLoughlin, L; Mutch, P; Gilboy, P; Miller, C; Broekema, M; Keogh, B; McCormack, W; et al. (Clinical pharmacology and therapeutics, 2013)
Upregulation of Toll‐like receptor 2 (TLR2) plays a critical role in inflammation associated with ischemia/reperfusion–induced tissue damage. OPN‐305 is the first humanized IgG4 monoclonal antibody against TLR2 in development and is intended for the prevention of reperfusion injury following renal transplantation and other indications. A phase I, single‐center, prospective randomized, double‐blind, placebo‐controlled study was performed to evaluate single ascending doses of OPN‐305 in 41 healthy male subjects (age range: 19–58 years) randomized to OPN‐305 or placebo across six cohorts. OPN‐305 was well tolerated across all doses, with no elevations in endogenous cytokines. A dose‐proportional increase in maximum serum concentration (Cmax) was observed, with area under the curve increasing in a greater‐than‐dose‐proportional manner with increasing elimination half‐life. OPN‐305 produced full TLR2 receptor blockade on CD14+CD45+ cells (monocytes), from 14 (0.5 mg/kg) to >90 (10 mg/kg) days, with a linear effect on the duration of inhibition of interleukin‐6 release after TLR2 stimulation. Clinical Pharmacology & Therapeutics (2013); 94 5, 593–600. doi:10.1038/clpt.2013.150